Analisis Pengaruh Variasi Kecepatan Putaran Mesin Peniris Minyak Terhadap Kualitas Penirisan Keripik Bayam Milik UMKM Jabal Dinar - Pernanda, Gustian; Yudo, Eko; Zulfitriyanto, Zulfitriyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Spinach chips are an innovative and healthy snack made primarily from spinach leaves mixed with flour and fried, where the oil-draining process plays a crucial role in determining the final product's quality. Home industries often rely on traditional methods, such as air-drying, although oil-draining machines have been introduced to Jabal Dinar SMEs. However, these machines require improvement due to excessively high and unstable rotation speeds. This study aims to identify the causes of instability and analyze the effects of varying rotation speeds (300, 400, 500 rpm) and draining durations (40, 60, 80 seconds) on product quality. The results indicate that the optimal speed is 400 rpm with a draining duration of 80 seconds, achieving a final weight of 77% while maintaining the texture and crispness of the spinach chips without breaking. In contrast, a speed of 500 rpm removes more oil, but the excessive centrifugal force damages the product due to the chips' thin and fragile nature.